Fabrication of metal mesh flexible transparent electrodes and heaters by a cost-effective method based on ultrafast laser direct writing. (June 2021) - Wang, Yi-lun; Li, Bao-jia; Li, Shuang-shuang; Huang, Li-jing; Wang, Yong-ying; Ren, Nai-fei
Graphical abstract: Highlights: Laser direct writing was used to fabricate completely embedded metal mesh on PET. Laser-etched grooves with small widths were obtained by optimizing laser parameters. The silver mesh transparent electrode (TE) had excellent photoelectric properties. The TE-based flexible transparent heater (FTH) showed stable heating performance. Abstract: A new ultrafast laser direct writing process to fabricate completely embedded silver mesh flexible transparent electrodes (TEs) using sputtered silver thin films and their applications for flexible transparent heaters (FTHs) are reported. The optimal laser etching parameters were determined, and the effects of mesh pitch and height on photoelectric properties of the silver mesh flexible TEs were systematically studied, with an aim to obtain a TE with excellent comprehensive performance. The resulting TE had a lower sheet resistance (0.86 Ω/sq) and a higher optical transmittance (91.26%) than traditional TEs. Good environmental stability of the TE, i.e. maintaining good electrical conductivity in air or deionized water without significant changes for 40 days, was also demonstrated. The fabricated representative FTH also presented stable heating performance, reaching a high temperature in 60 s under a DC voltage of 1.0 V and finally stabilizing at 98 ℃. This heating performance was confirmed to be stable and consistent after 20 cycles or under the conditions of bending and twisting. In addition, a deicing experiment was performed to illustrate the possible application of the FTH. The results indicated the availability of the laser direct writing method for fabricating high-performance metal mesh-based flexible TEs.